Exploring Language Effects In Ethnic Advertising: In Malaysian Environment - Yap, Eit Thian (1998)
This study applies sociolinguistic theories of accommodation to investigate how consumers in different cultures respond to the use of their etlmic language in advertising. Specifically, this study involved two dominant cultures in Malaysia, Malaysian Malay and Malaysian Chinese. In addition, this study also investigated the relationship between demographic factors such as age, gender, marital status, income, and education level and affect toward advertisements that used Bahasa Malaysia and English (for Malay respondents), and Chinese and English (for Chinese respondents).